Food Habits and Their Influence on Learning - Moreno, Luz Adriana Corrales; Zambrano Montes, Lubis Carmita (International Journal of Psychosocial Rehabilitation, 2020)
Currently, it is necessary for students to receive a balanced diet, according to the different stages of their development that benefits school learning. The eating habits acquired by different social, economic and cultural factors, could favor or alter the intake of nutrients necessary for the intellectual development and nutritional status of the infant, especially in rural and peri-urban areas where the acquisition and consumption of food is limited. Especially in different developing countries. The objective of this work is to analyze eating habits and their influence on student learning in middle childhood. Bibliographic, inductive-deductive and analytical review methods were applied. It is concluded that adequate nutrition positively influences learning and that eating habits are built in the school stage being conditioned to socio-cultural and economic aspects of families.